Ion specific effects on the immobilisation of charged gold nanoparticles on metal surfaces. Issue 3 (5th January 2018) - Kaulen, C.; Simon, U.
Abstract : Different monovalent cations influence the immobilisation of carboxylic acid and amine terminated gold nanoparticles. Abstract : Since the pioneering work of F. Hofmeister, Arch. Exp. Pathol. Pharmakol., 1888, 24, 247, ion specific effects have been steadily reported in the context of colloidal or protein stabilisation in electrolyte solutions. Although the observed effects are omnipresent in chemistry and biology, their origin is still under ferocious discussion. Here, we report on ion specific effects affecting the self-assembly of amine and carboxylic acid functionalised gold nanoparticles on metal surfaces as well as in electrolyte solution as a function of the monovalent cations Li +, Na +, K + and Cs + . Mercaptooctanoic acid and 1, 8-amine-octanethiol functionalised gold nanoparticles were adsorbed on structured AuPd/Pt substrates under addition of the respective chloride salts. Furthermore, the influence of the same salts on the salt induced aggregation of these AuNP was investigated. Our results demonstrate that the assembly processes on the metal surface as well as in electrolyte solution are influenced by the addition of different cations. We attribute the observed effects to ion pairing of the functional end groups with the added cations. With these findings we introduce a new parameter to control the self-assembly of 2D AuNP arrays on solid supports or of 3D AuNP networks in solution, which could be of relevance for the fabrication of new tailor-made functional materials or for biomedical applications.